2017
DOI: 10.1021/acs.jnatprod.7b00789
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Containing Volatiles from Marine Salinispora pacifica and Roseobacter-Group Bacteria

Abstract: Bacteria can produce a wide variety of volatile compounds. Many of these volatiles carry oxygen, while nitrogen-containing volatiles are less frequently observed. We report here on the identification and synthesis of new nitrogen-containing volatiles from Salinispora pacifica CNS863 and explore the occurrence in another bacterial lineage, exemplified by Roseobacter-group bacteria. Several compound classes not reported before from bacteria were identified, such as dialkyl ureas and oxalamides. Sulfinamides have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…The mass spectra resembled those of (E)-N-(3-methylbutyl)-1-phenylmethanimine ( Fig. 1C; Table 1), but with a shift of the intense ions m/z 91 and 118 in the latter to m/z 92 and 119 in the newly identified pear compounds (Harig et al 2017). This shift suggested the target compounds to be imines, derived from 3-pyridinecarboxaldehyde present in the pear volatiles.…”
Section: Identification Of Novel Componentsmentioning
confidence: 72%
See 3 more Smart Citations
“…The mass spectra resembled those of (E)-N-(3-methylbutyl)-1-phenylmethanimine ( Fig. 1C; Table 1), but with a shift of the intense ions m/z 91 and 118 in the latter to m/z 92 and 119 in the newly identified pear compounds (Harig et al 2017). This shift suggested the target compounds to be imines, derived from 3-pyridinecarboxaldehyde present in the pear volatiles.…”
Section: Identification Of Novel Componentsmentioning
confidence: 72%
“…Most pear cultivars (Pyrus communis L.) rely on insect pollination, as flowers are self-incompatible (Schanderl 1937;Schumacher 1989;Free 1993;Delaplane et al 2000;Jackson 2003). The Western honey bee (Apis mellifera L.) occurs in most of the (commercial) orchards and is overall the most important pollinator of pear (Stephen 1958;McGregor 1976;Free 1993;Delaplane et al 2000;Jackson 2003;Monzón et al 2004). Only in some orchards is the solitary bee Osmia cornuta used as managed pollinator, and in these cases as effective as the honey bee (Monzón et al 2004).…”
Section: Chemoecologymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Schulz-Bohm et al have shown that volatile compounds can diffuse within 20 minutes over distance of >12cm, which is a veritable distance for most soil microorganisms [11]. Despite their mostly hydrophobic nature, volatiles are widely produced in both terrestrial and aquatic environments by marine plankton, algae, animals and marine bacteria [12][13][14][15].…”
Section: Microbial Chemical Diversitymentioning
confidence: 99%